The family Solanaceae Juss. in the municipality of Vitória da Conquista, Bahia, Brazil - Moura, Jerlane Nascimento (2021)
Solanaceae is one of the largest families of vascular plants, with 100 genera and ca. 2,500 species, with subcosmopolitan distribution and greater diversity in the Neotropical region. This work carried out a floristic survey of Solanaceae species in the municipality of Vitória da Conquista, Bahia, in an ecotonal area between Caatinga and Atlantic Forest. Weekly collections were carried out from August/2019 to March/2020, totaling 30 specimens, deposited in the HUESBVC and HVC herbaria. Nineteen species were registered, distributed in nine genera: Brunfelsia (2 spp.), Capsicum (1 sp.), Cestrum (1 sp.), Datura (1 sp.), Iochroma (1 sp.), Nicandra (1 sp.), Nicotiana (1 sp.), Physalis (1 sp.) and Solanum (10 spp.). Among the species collected, five are endemic to Brazil and 11 were new records for the municipality. Our results demonstrate that Solanaceae is a family of high species richness in the municipality, contributing to the knowledge of the local flora.